Refining Data by Pointing the Index Finger (Cinéma & Cie. Film and Media Studies Journal, 2020)
This essay argues that data analysts refine data that is rendered visible through data visualizations by pointing the index finger. On the basis of an observation made from Werner Herzog’s documentary Lo and Behold: Reveries of the Connected World (2016), I argue that pointing makes the voice of data accessible through communicative reading and modeling work. Pointing is applied as an embodied method for cinematic knowledge production. The essay also proposes that the history of the invisible hand, introduced as market metaphor by Adam Smith, has to be updated by film and media studies and must be written towards active knowing processed through fingers. This article brings together perspectives from the history of art, media culture, social and economic theory.